The IS Curve and Monetary Policy Transmission in India: A New Keynesian Perspective. (February 2018) - Salunkhe, Bhavesh; Patnaik, Anuradha
The present study assesses the empirical performance of the new Keynesian IS model by estimating the standard as well as extended specifications of both the backward-looking and hybrid models in India over the period 1998Q1 to 2015Q4. It is found that the backward-looking IS model fits the data quite well in comparison with the hybrid model. The link between the policy rate and output gap appeared to be a bit stronger in the extended backward-looking IS model, as the interest rate coefficient is larger. Also, besides the interest rate, the real exchange rate, external demand and crude oil prices also have an impact on aggregate demand. The results suggest that the standard specification of the IS curve is inadequate to estimate the impact of the interest rate on aggregate demand and therefore a broader framework which accounts for additional variables besides the interest rate may be required. JEL Classification: E520, E120, C360, E510